Post-treatment vascular leakage and inflammatory responses around brain cysts in porcine neurocysticercosis. - Siddhartha Mahanty; Miguel Angel Orrego; Holger Mayta; Miguel Marzal; Carla Cangalaya; Adriana Paredes; Eloy Gonzales-Gustavson; Gianfranco Arroyo; Armando E Gonzalez; Cristina Guerra-Giraldez; Hector H García; Theodore E Nash; et al. (PLoS Neglected Tropical Diseases)
Cysticidal treatment of neurocysticercosis, an infection of humans and pig brains with Taenia solium, results in an early inflammatory response directed to cysts causing seizures and focal neurological manifestations. Treatment-induced pericystic inflammation and its association with blood brain barrier (BBB) dysfunction, as determined by Evans blue (EB) extravasation, was studied in infected untreated and anthelmintic-treated pigs. We compared the magnitude and extent of the pericystic inflammation, presence of EB-stained capsules, the level of damage to the parasite, expression of genes for proinflammatory and regulatory cytokines, chemokines, and tissue remodeling by quantitative PCR assays between treated and untreated infected pigs and between EB-stained (blue) and non stained (clear) cysts. Inflammatory scores were higher in pericystic tissues from EB-stained cysts compared to clear cysts from untreated pigs and also from anthelmintic-treated pigs 48 hr and 120 hr after treatment. The degree of inflammation correlated with the severity of cyst wall damage and both increased significantly at 120 hours. Expression levels of the proinflammatory genes for IL-6, IFN-γ, TNF-α were higher in EB-stained cysts compared to clear cysts and unaffected brain tissues, and were generally highest at 120 hr. Additionally, expression of some markers of immunoregulatory activity (IL-10, IL-2Rα) were decreased in EB-stained capsules. An increase in other markers for regulatory T cells (CTLA4, FoxP3) was found, as well as significant increases in expression of two metalloproteases, MMP1 and MMP2 at 48 hr and 120 hr post-treatment. We conclude that the increase in severity of the inflammation caused by treatment is accompanied by both a proinflammatory and a complex regulatory response, largely limited to pericystic tissues with compromised vascular integrity. Because treatment induced inflammation occurs in porcine NCC similar to that in human cases, this model can be used to investigate mechanisms involved in host damaging inflammatory responses and agents or modalities that may control damaging post treatment inflammation.